Cetuximab in the management of nasopharyngeal carcinoma – a narrative review. Issue 10 (11th September 2019) - Iqbal, M S; Wilkinson, D; Tin, A; Bossi, P; Gradwell-Nelson, L; Kovarik, J; O'Hara, J; Kelly, C
Abstract: Background: Concurrent chemotherapy with radiotherapy is the standard treatment for locoregionally advanced nasopharyngeal cancer. Cetuximab can be used in the treatment of head and neck squamous cell carcinoma. However, the randomised studies that led to approval for its use in this setting excluded nasopharyngeal cancer. In the context of limited data for the use of cetuximab in nasopharyngeal cancer in the medical literature, this review aimed to summarise the current evidence for its use in both primary and recurrent or metastatic disease. Method: A literature search was performed using the keywords 'nasopharyngeal neoplasm', 'cetuximab' and 'Erbitux'. Results: Twenty studies were included. There were no randomised phase III trials, but there were nine phase II trials. The use of cetuximab in the treatment of nasopharyngeal carcinoma has been tested in various settings, including in combination with induction chemotherapy and concurrent chemoradiotherapy, and in the palliative setting. Conclusion: There is no evidence of benefit from the addition of cetuximab to standard management protocols, and there is some evidence of increased toxicity. There is more promise for its use in metastatic or locally recurrent settings. This review draws together the existing evidence and could provide a focus for future studies.